The Potential of Herbal Agents for Hair Growth: A Mechanism-Based Review of Hair Follicle Stimulation - Budastra, Wayan Cintya Ganes (Jurnal Biologi Tropis, 2025)
Hair loss is a common condition that can negatively impact an individual’s psychological well-being and overall quality of life. Recent studies have shown that secondary metabolites derived from herbal plants possess potential as natural agents to stimulate hair growth. This review aims to provide a scientific basis for the development of herbal-based hair growth formulations in the future. The literature reviewed was sourced from major scientific databases such as PubMed, Scopus, ScienceDirect, and Google Scholar, with a focus on publications from the last ten years. This review discusses various groups of bioactive compounds including flavonoids, alkaloids, phenolics, polyphenols, phenylpropanoids, and saponins that play a role in follicle regeneration and alopecia prevention. The pharmacological effects of these compounds occur through several mechanisms, such as prolonging the anagen phase of the hair cycle, inhibiting the enzyme 5-α-reductase, enhancing blood circulation via vasodilation, and exhibiting strong antioxidant and anti-inflammatory activities. Findings from in vitro and in vivo studies indicate that these natural compounds show promise in promoting hair growth, although further clinical trials are needed to confirm their efficacy.